Gamification as a tool for increasing the depth of student understanding using a collaborative e-learning environment. (1st January 2013) - Betts, Ben W.; Bal, Jay; Betts, Alan W.
This paper briefly describes a collaborative learning environment created to improve participation in online learning. The environment, called Curatr, utilised the notion of game-like behaviours, colloquially known as 'gamification', to shape learners behaviour towards participating in social and collaborative learning activities, such as commenting, sharing and peer-marking. In the case study described, 33 students made 6, 152 contributions during a six-month part-time online continuing education course. Findings suggest that the number of 'experience points' a student earns on the platform is highly correlated with the average assignment mark they achieve (r = 0.499 n = 33). The results suggest that gamification can help improve the learning experience and the resulting performance for groups of students. There are limitations to this finding. Within the group there are cases where contribution and resulting performance do not correlate. Further work assessing the quality of contributions is suggested to understand this effect better.